Gambaran Cara Pencucian Alat Makan dan Keberadaan Escherichia coli Pada Peralatan Makan Di Rumah Makan - Anisa T Lubis; Oksfriani Jufri Sumampouw; Jootje M.L. Umboh (Universitas Sam Ratulangi, 2020)
Backgroud: The role of cleaning or washing equipment needs to be fundamentally known. By cleaning the equipment properly, it will produce food processing equipment that is clean and healthy. In the city of Manado cases of the diarrheal disease were reported in 2018 totaling 751 diarrhea sufferers. Based on data from the Tikala Baru Health Center, cases of diarrhea have increased in 2017-2019. In 2017 there were 46 cases, in 2018 there were 138 cases and in 2019 164 cases. The purpose of this research was to determine the technique of washing food equipment that is found in the Restaurant Tikala Baru Manado. Method: This research is a descriptive survey. This research was conducted at the restaurant Tikala Baru Village, in October-December 2019. The population in this study were 4 restaurants in the Tikala Baru Village. Sampling to determine the presence of E.coli in food equipment using a purposive sampling method. With samples for food utensils determined only on plates, cups, spoons, and forks. With a total of 16 samples. Laboratory tests are carried out at the North Sulawesi Regional Health Laboratory Office. Result: Based on laboratory tests conducted at the Tikala Baru restaurant, showed that from 16 samples that had been examined (1 cutlery was positive containing Escherichia coli bacteria) Conclusion: That overall, based on the technique of washing food equipment that is found in the Restaurant Tikala Baru still does not meet the requirements and has an E. coli.